The Effect of Scanning Technique on The Students’ Reading Comprehension on Narrative Text at the Eleventh Grade of SMA Tunas Bangsa in Academic Year 2018/2019 - Siti Hotimah; Achmad Fachrurrozy (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2020)
ABSTRACT This study applied principle of quantitative with quasi experimental design. The result of this study showed that scanning technique can give an effect towards students' reading comprehension. It can be seen from the value of pre-test and post-test. In control class, students' reading comprehension score for pre-test is 27,11 and for experiment class pre-test is 35,05. Meanwhile the post-test score for control class is 35,56 and experiment class is 51,10. the mean result of post-test for Experiment class is higher than control class. So it can conduded that scanning technique can give an effect toward students' Reading Comprehension. Moreover this technique can be implemented for the teachers in teaching reading and other skill in English. The teachers should be creative in developing material and task for students in order to improve students' skill in English